Highly Sensitive and Selective Sensors for CF4 Gas Molecules Based on Two‐Node Hollow Fullerene. Issue 20 (21st September 2020) - Zhang, Lishu; Li, Tao; Feng, Yuan Ping; Li, Hui; Shen, Lei
Abstract: Hollow nanostructures are widely used in chemistry, materials, and bioscience due to their excellent electrochemical and photoelectric properties. Recently, hollow fullerene nanostructures with tailored opening and shapes have been synthesized. Here, the transport properties of two‐node hollow‐fullerene‐based nanoelectronic devices, and their performance are studied for sensing the greenhouse gas molecule, CF4, by density functional theory combined with nonequilibrium Green's function formalism. It is found that such a device has a high sensitivity to CF4 molecules in both dry and humid environments owing to its good selectivity to H2 O molecules. The microscopic physics responsible for these fascinating properties are investigated by the transmission spectra, density of states, and voltage drop. This work paves a way to build new functional electronic devices based on the newly discovered hollow nanostructures. Abstract : Recently, hollow fullerene nanostructures with tailored opening and shapes have been synthesized. The transport properties of two‐node hollow‐fullerene‐based nanoelectronic devices, and their performance for sensing greenhouse gas molecule CF4, are studied. Such a device has a high sensitivity to CF4 molecules in both dry and humid environments.